Ferroptosis and bone health: bridging the gap between mechanisms and therapy - Xiao, Renyan; Han, Zhongyu; Jia, Peng; Li, Pei; Gong, Meng; Cai, Yijin; Pang, Lina; Ye, Xiangyin; Jin, Song (Frontiers in Immunology, 2025)
Ferroptosis is a novel type of programmed cell death that was discovered in recent years and is closely associated with disorders in iron cycling, abnormal lipid metabolism, excessive intracellular reactive oxygen species, and cellular antioxidant-related signaling pathways. Numerous studies have shown that ferroptosis plays a critical role in the development and progression of bone and joint diseases, although the underlying mechanisms remain incompletely understood. This review aims to outline the relevant mechanisms of ferroptosis, its implications in the bone microenvironment, and the mechanisms of action and therapeutic perspectives of ferroptosis in common bone and joint diseases, with the goal of informing future clinical research and treatment strategies targeting ferroptosis under these conditions.